Signal enhancement through heteronuclear polarisation transfer in in-vivo 31P MR spectroscopy of the human brain - Weber-Fahr, Wolfgang; Bachert, Peter; Henn, Fritz A.; Braus, Dieter F.; Ende, Gabriele (Magnetic resonance materials in physics, biology and medicine, 2003)
Significant 31P NMR signal enhancement through heteronuclear polarisation transfer was obtained in model solutions and in vivo on a 1.5-T whole-body MR scanner equipped with two RF channels. The much higher population differences involved in proton Zeeman energy levels can be transferred to the 31P levels with the refocused INEPT (insensitive nucleus enhancement by polarisation transfer) double-resonance experiment by means of a series of simultaneously applied broadband RF pulses. INEPT achieves a polarisation transfer from 1H to 31P spin states by directly reordering the populations in spin systems with heteronuclear scalar coupling. Thus, only the 31P NMR signal of metabolites with scalar 1H-31P coupling is amplified, while the other metabolite signals in the spectra are suppressed. Compared to Ernst-angle excitation, a repetition-time-dependent signal enhancement of η=(29±3)% for methylene diphosphonic acid (MDPA) and η=(56±1)% for phosphorylethanolamine (PE) was obtained on model solutions through optimisation of the temporal parameters of the pulse experiment. The results are in good agreement with numerical calculations of the theoretical model for the studied spin systems. With optimised echo times, in-vivo 31P signal enhancement of the same order was obtained in studies of the human brain.
Im Texst ist die "31" hochgestellt
Gesehen am 03.11.2020